2009
DOI: 10.4052/tigg.21.13
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Analysis of Cellobiohydrolase: Quantification of Enzymatic Reaction at a Solid/Liquid Interface Applying the Concept of Surface Density

Abstract: In nature, crystalline cellulose is mainly degraded by cellobiohydrolases (CBHs) produced by various microorganisms. Since both substrate and enzymatic features relate to the reaction and the reaction proceeds at a solid/liquid interface, it is quite di‹cult to perform the quantitative analysis of CBH. In the present study, we estimate the surface area of crystalline celluloses by the adsorption maxima (Amax) of CBH, the speciˆc activity of CBH (k=v/A) was plotted versus surface density ( r= A/Amax) to adjust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“… 1) Cellulose-degrading microbes typically utilize hydrolytic enzymes called cellulases and β-glucosidases to obtain glucose, the repeating unit of cellulose, as an energy source. 2) 3) 4) 5) 6) 7) 8) Although these enzyme reactions require only water molecules, Eriksson and coworkers found that the rate of cellulose decomposition by filamentous fungal cellulases was greater in an oxygen atmosphere than in a nitrogen atmosphere, clearly indicating a contribution of oxidation to cellulose degradation by fungi. 9) 10) 11) 12) 13) 14) 15) Indeed, an oxidative enzyme named cellobiose dehydrogenase (CDH: EC 1.1.99.18), initially known as cellobiose oxidase (CBO: EC 1.1.3.25), was discovered in cellulolytic cultures of the wood-rotting fungus Sporotrichum pulverulentum , an anamorph of Phanerochaete chrysosporium .…”
Section: Introductionmentioning
confidence: 99%
“… 1) Cellulose-degrading microbes typically utilize hydrolytic enzymes called cellulases and β-glucosidases to obtain glucose, the repeating unit of cellulose, as an energy source. 2) 3) 4) 5) 6) 7) 8) Although these enzyme reactions require only water molecules, Eriksson and coworkers found that the rate of cellulose decomposition by filamentous fungal cellulases was greater in an oxygen atmosphere than in a nitrogen atmosphere, clearly indicating a contribution of oxidation to cellulose degradation by fungi. 9) 10) 11) 12) 13) 14) 15) Indeed, an oxidative enzyme named cellobiose dehydrogenase (CDH: EC 1.1.99.18), initially known as cellobiose oxidase (CBO: EC 1.1.3.25), was discovered in cellulolytic cultures of the wood-rotting fungus Sporotrichum pulverulentum , an anamorph of Phanerochaete chrysosporium .…”
Section: Introductionmentioning
confidence: 99%